Pedagogical socio-affective possibilities from orality, reading and writing to improve the community relations in a Ciudad Bolívar school in Bogotá (Papeles, 2017)
The present paper is directed from ideas that are support from socio-affectivity to develop pedagogical possibilities that are a contribution to improve the community relations of the students of fifth grade in the Maypore Educational Institution, located in Ciudad Bolívar, in the city of Bogotá. This project was carried out through the following phases: first, observation, which was supported thanks to the field diary; second, bibliographic review from socio-affective theories, likewise the ideas that the peace program, academic harmony, language skills and others, which contributed to the construction of the pedagogical possibilities; third, the elaboration andapplication of student’s workshops from the following language skills: oral, readingand writing.
Keywords: academic harmony; socio-affective; oral; reading; writing